Concept of Siddhars Aimed at Healthy Longevity - Prof. Dr.S.N. Sugumar, Dr.M.P.Agathiyar (International Journal of Advanced Science and Technology, 2020)
The concept of healthy longevity exploration from the siddha philosophy counterparts that Siddhar principles of preventing illness makes human body resilient naturally as point out in “Theraiyar Pini Anugaa Vidhi”. Today, due to the ignorance in sustaining health one can easily get hold of disabilities, disorders and disease. At the core of healthy ageism and many years of probable longevity, healthy adults valued for depth of experienced knowledge can contribute meaningfully to their living society. Thus lessening old age dependency with longevity concepts would also influence substantial prospects with economic impact on monetary activity of our nation.